Reframing Urban Industrialization in the Sustainability Transition: Sustainable Urban Infrastructure, Brownfield Remediation, and Collaborative Urban Governance - Arie Wahyu Prananta; I Wayan Suyadnya; Indra Jaya Kusumawardana; Zainal Abidin (PT. Anagata Sembagi Education, 2026)
Urban industrialization is increasingly governed through sustainability-transition agendas, yet research remains divided between sustainable infrastructure, brownfield remediation, and collaborative governance literatures. This article addresses a specific gap: prior studies often treat infrastructure upgrading and land remediation as direct drivers of industrial outcomes, while the governance mechanism that converts physical and ecological interventions into coordinated industrial transformation remains under-specified. The study develops a four-construct SEM framework in which Sustainable Urban Infrastructure and Brownfield Remediation are theorized as exogenous constructs, Collaborative Urban Governance is specified as the mediator, and Urban Industrialization is the outcome. Using the available 455-case Excel dataset, the empirical component estimates a data-constrained proxy model with Industrialization Intensity (IND), Digital-Infrastructure Capability (DIC), and Socio-Economic Resilience (SER). CFA results show strong measurement quality, with loadings from 0.778 to 0.849 for IND, 0.804 to 0.835 for DIC, and 0.800 to 0.843 for SER; CR ranges from 0.901 to 0.914 and AVE from 0.646 to 0.681. The structural model fits well (chi-square/df = 2.108; CFI = 0.961; TLI = 0.951; RMSEA = 0.049; SRMR = 0.038). IND significantly predicts DIC (beta = 0.537), DIC predicts SER (beta = 0.424), and the indirect effect is significant (0.228; 95% CI [0.178, 0.282]). The article contributes a governance-mediated urban-industrial model and a transparent empirical reporting architecture for sustainability-transition research.